Takikardia Ventrikel Berulang Pasca Coronary Artery Bypass Grafting (CABG): Laporan Kasus Berbasis Bukti - Wijaya, Ika Prasetya; Salim, Simon; Nabila, Audina Dhiya (Jurnal Penyakit Dalam Indonesia, 2026)
Coronary artery bypass grafting (CABG) remains the treatment of choice for patients with complex multivessel coronary artery disease but carries a risk of serious perioperative complications, including ventricular arrhythmias such as ventricular tachycardia (VT). Although VT following CABG is rare, it is potentially life-threatening and often results from multiple interrelated factors. This report presents a case of recurrent ventricular tachycardia after CABG and to highlight the underlying mechanisms, risk factors, and evidence-based management strategies aimed at preventing adverse outcomes.We report a 54-year-old woman with diabetes, hypertension, prior myocardial infarction, and severe left ventricular dysfunction who underwent urgent CABG for three-vessel disease. Postoperatively, she developed recurrent VT associated with fluctuating electrolytes and early vein graft occlusion. Management included urgent graft revascularization, aggressive metabolic correction, repeated defibrillation, and intravenous antiarrhythmic therapy, resulting in VT cessation. Ventricular tachycardia following CABG illustrates the interplay between a vulnerable arrhythmogenic substrate and modifiable perioperative factors. Comprehensive perioperative monitoring, early identification of high-risk conditions, and prompt correction of reversible triggers are essential to prevent serious outcomes and improve prognosis in this patient population.